Addressing graduate employability - Ishak, Mohamed Mustafa (Star Publications (M) Bhd, 2014)
Youth unemployment is a pressing national concern. According to a 2012 report by the then Ministry of Higher Education, a quarter of all graduates were not able to secure employment upon graduation.